Microfinancing, governance, and performance: A South Asian perspective - Asif Saeed; Attiya Y. Javed; Umara Noreen (Journal of Economics, Finance and Administrative Science, 2018)
This paper aims to investigate the relationship between microfinance institutions (MFIs) governance and performance. Design/methodology/approach Using a sample of 215 MFIs from six South Asian countries over the period from 2005 to 2009, the authors examine the effect of chief executive officer (CEO) duality, board size, female CEO, urban market coverage, bank regulation and lending type on financial and social performance of MFIs. Findings The findings provide evidence that, on the one hand, empowered CEO, large board size and individual lending improve the MFI financial performance and, on another hand, bank regulation and serving in the urban market have a significant association with MFIs' social performance. In an additional analysis, the authors also test this relationship before, during and after the financial crisis of 2007. During crisis period, MFIs' individual lending reduces the operational cost and bank regulation increases the average loan size in South Asian MFIs. Originality/value Those studies that are presented in the literature review conclude their result on the bases of global, European, East African and specific to some countries sample. There is no study presented in the whole literature on South Asian sample, in which all countries really face the problem of poverty.
Keywords: G34; I32; L31; N85; 330; Corporate governance; Financial performance; South Asia; Social performance